Reliability and concurrent validity of the bubble inclinometer for visualestimation of straight leg raise in asymptomatic individuals - Somprasong, Sirikarn; Sakulsriprasert, Prasert; Vachalathiti, Roongtiwa; Kingcha, Pathaimas; Janyathitipath, Thanachaporn (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The straight leg raise (SLR) test is commonly used to investigate neurodynamic problems or hamstring musclelength. Visual estimation can be used to identify the degrees of hip flexion during the SLR test. However, intra-tester and intertester reliability, as well as concurrent validity, await formal investigation.Methods. This study was an experimental study. Two testers, a novice and an experienced physical therapist, measured hipflexion angles during the SLR test using visual estimation for two sessions and the bubble inclinometer method during the firstsession in 31 asymptomatic participants, in random order. Intra-tester reliability (intraclass correlation coefficient, ICC3,3), intertester reliability (ICC2,3), concurrent validity (Pearson correlation with bubble inclinometer), and measurement error was represented as standard error of measurement (SEM) and minimal detectable change (MDC), were calculated.Results. The concurrent validity and intra-tester reliability of visual estimation for both testers were good (ICC3,3 = 0.885 with 95%confidence interval = 0.775–0.943, p < 0.001) and excellent (ICC3,3 = 0.904 with 95% confidence interval = 0.810–0.952, p < 0.001),respectively. Inter-tester reliability of visual estimation was poor (ICC2,3 = 0.373 with 95% confidence interval = 0.027–0.639,p = 0.018).Conclusions. Although the concurrent validity of visual estimation with the bubble inclinometer was good, and intra-testerreliability was excellent, the inter-tester reliability was poor. Therefore, caution should be exercised if more than one tester is involved in visual estimation.
Keywords: reliability; straight leg raise; visual estimation